Analisis Praktik Penjualan Produk Pada Shopee dan TikTok Shop by Tokopedia; Potensi Pelanggaran Prinsip Ekonomi Syariah Dalam E-Commerce - Refania Meilani Firdos; Muh Ilham Wahyu Fajar; Nazhifah Maulia (JPIES: Jurnal Pelita Ilmu Ekonomi Syariah, 2025)
This study aims to analyze the practice of selling goods on online applications with a focus on potential violations of sharia economic principles. The growing number of online buying and selling transactions has resulted in various challenges in the implementation of sharia principles, especially related to the prohibition of gharar (uncertainty), riba (interest), and tadlis (fraud). This study uses an approach with a literature study method and interviews with online business actors to identify the forms of violations that occur and their mitigation efforts. The results of the study show that although many e-commerce platforms have attempted to implement the principles of fairness, openness, and halal products, there are still practices that have the potential to violate such as the dissemination of non-transparent information, fake product assessments, and the use of payment systems that contain elements of usury such as paylater. This study emphasizes the importance of increasing awareness of business actors and consumers regarding sharia economic principles and strengthening regulations so that online buying and selling practices can run in accordance with sharia values, creating a fair, transparent, and blessed e-commerce ecosystem.